(untitled) (Південний архів (історичні науки), 2022)
The article analyzes the European integration of the Republic of Moldova, in particular cooperation with the European Union within the “Eastern Partnership” program. The dynamics of foreign policy orientations through bilateral agreements signed in the period from 2009 to 2020 are traced. The key problems that arose in the process of cooperation are characterized. All achievements of the country, which affect its current economic and social opportunities, are analyzed separately. The positions of the thematic platforms within the framework of economic cooperation between Moldova and the European Union, in particular within the framework of the Eastern Partnership, were considered. The purpose of the article is to analyze the cooperation of the Republic of Moldova with the initiative of the European Union “Eastern Partnership”. The main task of the article is to highlight the state of cooperation between the Republic of Moldova and the European Union within the Eastern Partnership. Research methods. During the research, the method of analysis was used, with the help of which the cooperation between the Republic of Moldova and the European Union in the “Eastern Partnership” initiative was highlighted. In the process of researching the state of bilateral cooperation between Moldova and the European Union, inductive and deductive methods were used. Methods of synthesis and generalization were used to determine the structure of cooperation at the bilateral and regional levels. The results. It has been established that the Republic of Moldova has come a long and thorny way within the framework of the Eastern Partnership. The country participates in a number of programs developed by the European Union, which make it possible to monitor the success of the tasks assigned to the state and to provide assistance in every way if necessary. Such cooperation takes place in a bilateral format and at the regional level. Over 10 years of such cooperation, Moldova has significantly advanced in the direction of the European Union, and in the coming decade their cooperation will become even closer. Conclusions. In the course of the study, it was found that the relations between the European Union and the Republic of Moldova within the framework of the “Eastern Partnership” initiative are deep and multifaceted. The country participates in many agreements and programs of the European Union. Both sides are deepening relations within the framework of the Association Agreement. The parties cooperate in the context of the Deep and Comprehensive Free Trade Agreement. Within the framework of the Eastern Partnership, member states provide significant support to the Republic of Moldova in the security sector and EUBAM (European Union Border Assistance Mission to Moldova and Ukraine). The European Union is interested in cooperating with Moldova, because it seeks to have reliable neighbors on its eastern borders, which will ensure its own security and further prosperity. The European Union seeks to improve democracy, ensure the rule of law and respect for human rights in the Republic of Moldova, as well as contribute to the improvement of IT security and the fight against IT crime, strengthen measures to prevent natural disasters.